New Eocene damselflies and first Cenozoic damsel-dragonfly of the isophlebiopteran lineage (Insecta: Odonata) - Garrouste, Romain; Nel, André (Zootaxa, 2015)
The study of a new specimen of Petrolestes hendersoni from the Eocene Green Formation allows a more precise description of the enigmatic damselfly and the diagnosis of the Petrolestini. Petrolestes messelensis sp. nov. is described from the Eocene Messel Formation in Germany, extending the distribution of the Petrolestini to the European Eocene. The new damsel-dragonfly family Pseudostenolestidae is described for the new genus and species Pseudostenolestes bechlyi, from the Eocene Messel Formation. It is the first Cenozoic representative of the Mesozoic clade Isophlebioptera.